Investment Feasibility Analysis of Procuring an Ultrasonography (USG) Machine at Griya Hayati Clinic Using Break-Even Point, Payback Period, and Net Present Value Methods - Faya Anggun Mustikaningtyas; Mohammad Sofyan; Muhammad Imron (International Journal of Business and Quality Research, 2026)
The healthcare industry, particularly small clinics, faces significant financial risks when procuring high-cost diagnostic equipment due to the uncertainty of cash flows and limited capital. While previous studies have addressed investment feasibility in large-scale hospitals, studies addressing the financial feasibility of medical equipment in independent pain clinics remain scarce. Therefore, this study examines the financial feasibility of procuring an Ultrasonography (USG) machine at Griya Hayati Clinic in Madiun, Indonesia. A quantitative descriptive research design was adopted, while saturated sampling was used to analyze the entire data related to the investment plan over a 5-year economic life projection. Secondary data were collected through document analysis and structured interviews with the clinic's management, and analyzed using three financial appraisal methods: Break-Even Point (BEP), Payback Period (PP), and Net Present Value (NPV). The result demonstrated that the investment is highly feasible. Specifically, the BEP is reached at 306 patients per year, offering a high Margin of Safety of 74.5%. Furthermore, the PP is achieved within 1 year, 4 months, and 2 days, which is significantly shorter than the machine's 5-year economic life. The NPV yielded a positive value of IDR 779,651,010 at a 10% discount rate. The study concludes that the procurement of the USG machine is highly feasible and financially viable for the clinic. The study recommends that the clinic management should immediately realize the investment and maintain its operational performance to meet the target patient volume.